Degradation assessment of 1.2-kV SiC MOSFETs and comparative study with 1.2-kV Si IGBTs under power cycling. (May 2022) - Chen, Yuan; Huang, Hong-Zhong; Rao, Yunliang; He, Zhiyuan; Lai, Ping; Chen, Yiqiang; Xu, Xinbing; Liu, Chang
Abstract: Although SiC MOSFETs has better performance than Si IGBTs, some obvious differences between SiC materials and devices and Si equivalents affect the robustness and reliability of SiC MOSFETs. In this paper, an in-depth comparison of degradation assessment of 1.2-kV SiC MOSFETs and 1.2-kV Si IGBTs under the same power cycling test condition is presented. The variations of electrical and thermal characteristics of the two kinds of devices are investigated comparatively. Both devices chip-related and package-related degradation analysis is provided to explain each parameter variation. And a detailed physical analysis is conducted to have a better understanding of the root cause of the aging. From test results, SiC MOSFETs with the same package process will fail earlier than Si IGBTs. After a long period of PCT, Si IGBTs are not observed other failure modes except for solder layer degradation, but SiC MOSFETs are successively observed three failure modes: solder layer crack and delamination, bond crack, threshold voltage shift. However, chip-level degradation failures are much later than package-level degradation failures for SiC MOSFETs. It is shown that although chips still have unresolved reliability problems for SiC MOSFETs, the package reliability is the shortcoming that limits their long-term service life. Highlights: The degradation mechanism of SiC MOSFET and Si IGBT under PCT was compared comprehensively. The relationship between the stresses and failures was found. The package is the shortcoming that limits SiC MOSFETs long-term service life.